Strategi Konvergensi media Cetak dan Media Online - Catharina Susy Triputranti (LPPM Universitas Pramita Indonesia, 2023)
Media convergence is the only way for media existence to be maintained in the present, which is people in consuming media also change. Media convergence strategies and practices have become demands in the era of information invasion. The purpose of this study is to determine the convergence strategy carried out by the media industry in maintaining the media business to remain productive and sustainable. While the problem that often arises is the demands of the multitasking journalist profession which is not as smooth as expected. The convergence journalist profession must have multiskills using technology and writing technology news. However, convergence is one of the old media strategies to maintain its existence amid the rapid development of internet technology. This research will use a qualitative approach with literature study methods and data collection techniques through observation from various sources, both from previous research results, as well as publications from various media and related theories. The results of the study want to know the convergence processes and strategies carried for the sustainable media industry. Although there is strategy different of some research results, there are still similarities that state that whether they like it or not, the media must adapt to increasingly rapid technological developments by conducting media convergence for sustain. Key Words: Convergence, Media Strategy, Print media, Online Media, Media Industry